The effect of laboratory procedures and repeated-glazing on color of metal-ceramic restoration - Hatice Özdemir; Zeynep Yesil Duymus (Wolters Kluwer Medknow Publications, 2019)
Background: Routine laboratory procedures and repeated glazed effect the final color of metal-ceramic restorations (MCRs). Clinicians wonder if the color changes after routine laboratory procedures and repeated glazed is clinically acceptable or not. Aims: The aim of this study was to determine the color changes of MCRs after routine laboratory procedures and then glazed for 1, 2, and 3 times. Materials and Methods: Forty-five disc-shaped (10-mm diameter and 1-mm thickness) specimens were fabricated from Cr-Co metal-alloy. Bonding agent, first and second layer of shade A2opaque porcelain (OP) were applied on the metal specimens. The color of specimens was measured with a spectrophotometer after each procedure and △E1, △E2,and △E3values were calculated. Shade A2feldspathic porcelain was applied (2-mm thickness) to all specimens. Glaze was applied on the porcelain for 1, 2, and 3 times and then, the color measured after each procedure and △E4, △E5, and △E6values were calculated. Data were analyzed with one-way ANOVA and Duncan test (P < 0.05). Results: △E1that was obtained between the first layer of OP and bonding agent showed the greatest value. △E2that was obtained between the second and first layer of OP showed the lowest value. After repeated glazed procedures, the final color of the specimens was changed; but, these changes were clinically acceptable (△E < 5.5). Conclusions: The routine laboratory procedures and glazed for 1,2, and 3 times is effect the color of MCRs; but, the color changes were clinically acceptable (△E < 5.5).